A Decolonial Perspective on the Practice of Unveiling Tombstones in Pentecostal and Charismatic Churches in South Africa - Mookgo Solomon Kgatle; Thinandavha Derrick Mashau (Religions, 2023)
Tombstone, the practice of demarcating a grave and unveiling it in some instances, has been common since ancient times. The practice is related to marking the grave in order to remember its geographical location, and subsequently for future generations to identify with it. This practice is very common in a South African context, especially in African traditional religion (ATR). In addition, they would have other ceremonies to revisit the grave and/or the tombstone of their loved one as a way of remembering them. However, some Pentecostal and Charismatic churches prohibit this practice as ancestral worship. This article argues that the erection and unveiling of tombstones does not necessarily need to be understood as ancestral worship. A distinction needs to be made between ancestral worship and ancestral commemoration in an African context. The conclusion is that when the practice of unveiling tombstones is carried out as a way of remembering and showing respect to our ancestors, but not worshiping and revering them, this practice should be supported by Christians from Pentecostal and Charismatic churches as well. There is therefore a need, from a decolonial perspective, to use the missional hermeneutics of discernment and naked truth to provide a proper biblical and acceptable Christian practice of the unveiling of the tombstone in the South African context.